DEVELOPING AN ENGLISH MODULE FOR ISLAMIC BOARDING SCHOOLS IN WEST NUSA TENGGARA - Puspita - Dewi (INOVISH JOURNAL, 2021)
The Islamic boarding schools need special materials, teaching methods, or media because Islamic boarding schools (IBS) have different cultures and educational system from students in regular schools in which some points of educational system and culture in IBS can be adopted in public education system such as personality, leadership, and authority (Hidayat in Hidayat, 2016). This study aims to identify the target needs, learning needs, and develop an appropriate English module for grade eleven students of Islamic Boarding Schools. The research method used in this study is Research and Development (R&D). The evaluation of the module used a questionnaire with ranging a 4-point Likert scale from 1 (disagree), 2 (fair), 3 (agree), and 4 (strongly disagree) with 40 items. The results of the questionnaire calculated in quantitative data conversion with four categories namely poor (1.00-1.75), fair (1.76-2.51), good (2.52-3.27) and very good (≥ 3.28). The results of the need analysis indicate that most students prefer topics of daily life, religion, and education. Each unit has eight components, namely: unit title, objectives, warm-up, main activities, summary, reflection, evaluation, feedback, and follow-up.  The first try-out of the second draft shows that the draft is needed to be revised since the average score is within the data interval of 2.52 ≤  ≤ 3.27. Meanwhile, the third draft is considered appropriate and applicable as indicated by average score within the interval of ≥ 3.28. The recommendation for future research is government and other scholars expected to design and develop textbooks that are relevant to Islamic values and contexts.